2013
DOI: 10.1002/pon.3413
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Japanese SHARE model in improving Taiwanese healthcare personnel's preference for cancer truth telling

Abstract: The SHARE model-centered CST programs significantly improved Taiwanese healthcare personnel's truth-telling preference. Future studies should objectively assess participants' truth-telling preference, for example, by cancer patients, their families, and other medical team personnel and at longer times after CST programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Thus, the Taiwanese‐version truth‐telling scale measures not only subjects' truth‐telling preferences but also their experiences of physicians' truth‐telling practice. This modified scale had good reliability when tested on 275 medical students and 257 health care providers . In this study, internal consistency (Cronbach's alphas) for the overall scale was .95, whereas internal inconsistencies for its subscales were .78‐.90 when measured in patients, family members, and physicians (Appendix A).…”
Section: Methodsmentioning
confidence: 72%
See 2 more Smart Citations
“…Thus, the Taiwanese‐version truth‐telling scale measures not only subjects' truth‐telling preferences but also their experiences of physicians' truth‐telling practice. This modified scale had good reliability when tested on 275 medical students and 257 health care providers . In this study, internal consistency (Cronbach's alphas) for the overall scale was .95, whereas internal inconsistencies for its subscales were .78‐.90 when measured in patients, family members, and physicians (Appendix A).…”
Section: Methodsmentioning
confidence: 72%
“…In this quantitative comparative study, the truth‐telling preferences of cancer patients, their families, and their doctors were compared with patients' and families' experiences of doctors' actual clinical truth‐telling practices. Truth telling was measured using the Taiwanese‐version modified Japanese truth‐telling scale, whose reliability and validity were acceptable in medical students and health care providers in Taiwan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SHARE scale is the scale of confidence in communicating bad news to patients with cancer (Fujimori et al, 2014b) and is used to measure effects of CSTs in doctors (Tang et al, 2014). There are 36 items, and the four subscales (Fujimori et al, 2014b).…”
Section: Share Scalementioning
confidence: 99%
“…Fujimori et al (Fujimori et al, 2014a) reported that communication skills based on patients' preferences comprised four elements, grouped into the acronym "SHARE": setting up a supportive environment for the interview [S (ENV)], considering how to deliver bad news [H (HOW)], discussing additional information [A (ADD)], and providing reassurance and responding empathically to the patient's emotions [RE 6 (EMP)]. In two studies (Fujimori et al, 2014b;Tang et al, 2014), CST developed based on patients' preferences for medical communication increased confidence of oncologists to communicate with cancer patients. Also, Razavi et al (Razavi et al, 2002) reported that this type of CST increased the use of emotional words by not only doctors but also nurses in communicating with patients with cancer.…”
Section: Introductionmentioning
confidence: 99%